A Cross Section Study to Determine the Prevalence of Antibodies against HIV Infection among Hepatitis B and C Infected Individuals - Flores, Geane L. (2016)
Fundação Oswaldo Cruz. Instituto Oswaldo cruz. Laboratório de Hepatites Virais. Rio de Janeiro, RJ. Brasil.